Increasing the Brand Awareness of Artotel Surabaya Using a Promotional Video - Sherin Gloria Ivanalim (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
The problem related to Business Communication that I found at ARTOTEL Surabaya is poor brand awareness compared to the other hotels which has a good brand awareness such as Pop Hotel, Cleo Business Hotel, and Oval Hotel. Because of this problem, the focus is on increasing the brand through the hidden uniqueness of ARTOTEL Surabaya. In this way, the promotional video will be the solution. The contents of ARTOTEL Surabaya’s promotional video are three USPand ending. The USPis about the location, the unique rooms, and the foods. There are some theories about brand awareness, branding, promotion, and promotional video. This promotional video can be a new innovation to promote the hotel since ARTOTEL Surabaya does not have a promotional video before. As a result, ARTOTEL Surabaya will have a good brand awareness as a hotel with a good hospitality and a touch of art.